PEMELIHARAAN ARSIP DI BAGIAN SATUAN LAYANAN ADMINISTRASI PADA KANTOR PERWAKILAN BANK INDONESIA WILAYAH SUMATERA SELATAN DI PALEMBANG - R.A Rodia Fitri Indriani (Pusat Riset dan Inovasi Nasional, 2022)
The location of the research by the author is in the Representative Office of Bank Indonesia Region of South Sumatra in Palembang. Methods of data collection are by interview and observation, while the analysis technique used by the author is descriptive analysis techniques. From the analysis of the authors on the maintenance of archives in the Unit of Administration Services Representative Office of Bank Indonesia Region of South Sumatra in Palembang has not been done well, there are still many documents or archives torn because the size of the archive is too large to be stored in owner or bundle temple and place archive storage still smelly and dusty. The advice given by the author is to keep the archives protected from destructive factors, do maintenance activities according to the rules of the archive, such as every day to clean the archive to avoid dust, giving camphor to prevent odor and prevent insects, and the large archive storage of the folder keeps it in a suitable place to keep the archive unfolded which results in a torn archive. That way the maintenance of a good archive will facilitate the archiving activities.